2005
DOI: 10.1038/sj.bjp.0706035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of synaptotagmin reveal two distinct mechanisms of agonist‐stimulated internalization of the M4 muscarinic acetylcholine receptor

Abstract: Synaptotagmin has been reported to function in clathrin‐mediated endocytosis. Here, we investigated its involvement in agonist‐stimulated internalization of M4 muscarinic acetylcholine receptors exogenously expressed in human embryonic kidney (HEK‐293 tsA201) cells. Synaptotagmin I was present at low levels in these cells, and when overexpressed resided at the plasma membrane. Synaptotagmin overexpression alone did not affect receptor internalization, but ‘rescued’ internalization that had been inhibited by ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…Other studies have implicated a similar ability of Syt I to recognize specific cargo, as was reported in the M 4 muscarinic receptor (27). In mouse L cells expressing high levels of transferrin receptor, specific targeting of AP2 to the receptor was observed prior to clathrin recruitment and assembly, although the basis of this interaction was not described (18).…”
Section: Discussionmentioning
confidence: 82%
“…Other studies have implicated a similar ability of Syt I to recognize specific cargo, as was reported in the M 4 muscarinic receptor (27). In mouse L cells expressing high levels of transferrin receptor, specific targeting of AP2 to the receptor was observed prior to clathrin recruitment and assembly, although the basis of this interaction was not described (18).…”
Section: Discussionmentioning
confidence: 82%
“…In neuronal cells, Syts are essential for mediating "fast vesicle" fusion for neurotransmitter release (1,17) but also function in endocytosis. Syt 1 regulates endocytosis of the acetylcholine receptor (25), a process that involves the AP2 complex before membrane internalization (12,13). Syt 7 appears to have a role in membrane sealing and lysosomal trafficking (9,26,27).…”
mentioning
confidence: 97%
“…In this type of homo-desensitization process, an endocytic pathway involving dynamin I and arrestin-2 is mainly responsible for M4R internalization. When dynamin I or arrestin-2 is functionally knocked out, synaptotagmin, a membrane-trafficking protein, can initiate ‘rescue’ and takes a full control of M4R internalization [12] . In the end, synaptotagmin, AP2, and M4Rs are suggested to form a ternary complex [12] , in which the M4R C-terminal motif “YRNI” is supposed to be a core sequence to interact with AP2.…”
Section: Interactions Of M4r With Non-enzymatic Proteinsmentioning
confidence: 99%